DETERMINAN PERILAKU PENCEGAHAN PERDARAHAN PASCA PERSALINAN - Harmatuti, Harmatuti (STIKes Medistra Indonesia, 2021)
Postpartum hemorrhage is still high in incidence due to the low prevention behavior during pregnancy. Several efforts that can reduce physical and psychological disorders such as promotion of a healthy life and early detection can be applied in strategies to prevent postpartum bleeding. This study aims to determine the effect of empowerment, the role of husbands, the role of peer groups, health status, knowledge and attitudes on the behavior of pregnant women in preventing postpartum hemorrhage at the Kesdam Cijantung Hospital in 2019. The research method used is quantitative with cross-sectional design. Data analysis using smartPLS 2.0 and SPSS 18. The results of hypothesis testing using Structural Equation Modeling (SEM) research findings are empowerment (16.58%), husband's role (4.8%), peer group role (18.30%), status health (24.37%), knowledge (10.07%) and attitudes (10.50%), the direct effect of the behavior of pregnant women in preventing postpartum bleeding was 84.61%, and the indirect effect was 1.1%. Health status is the dominant factor that greatly influences the behavior of pregnant women in preventing postpartum bleeding. Researchers suggest that several parties work together to assist pregnant women in preventing postpartum bleeding.